1944
DOI: 10.1002/qj.49707030402
|View full text |Cite
|
Sign up to set email alerts
|

On Wilson's theory of the collection of charge by falling drops

Abstract: Wilson's theory of the acquisition of charges by drops falling through a region containing ions is worked out in detail ; diagrams of the paths of ions and curves of the rates of acquisition of charge are drawn. The applications of the theory to the building up of fields in clouds and to the charging of raindrops are briefly discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

1947
1947
1987
1987

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(24 citation statements)
references
References 6 publications
2
22
0
Order By: Relevance
“…6 Table 1. List of formulations of charging rate on precipitation particle which are taken into account of the penetration effect and by Whipple and Chalmers (1944 it can reach where *<*1. And for a negative ion, from Eq.…”
Section: 2mentioning
confidence: 99%
See 2 more Smart Citations
“…6 Table 1. List of formulations of charging rate on precipitation particle which are taken into account of the penetration effect and by Whipple and Chalmers (1944 it can reach where *<*1. And for a negative ion, from Eq.…”
Section: 2mentioning
confidence: 99%
“…The rate of charge acquisition considering the penetration effect is derived in the same manner as Whipple and Chalmers (1944) by the equations of movement of the positive and negative ions. If t is eliminated from the Eqs.…”
Section: Appendix Derivation Of the Pe Formulationmentioning
confidence: 99%
See 1 more Smart Citation
“…One set of theories that does not primarily focus on microphysics includes ion convection (Grenet, 1947, Vonnegut, 1954, ion induction (Wilson, 1929;Whipple and Chalmers, 1944) and polarization charging (Elster and Geitel, 1913;Mason, 1972). Other theories are highly dependent on microphysics -water drop breakup (Simpson, 1909), splashing of water drops on ice (Workman and Reynolds, 1950), melting of ice (Dinger and Gunn, 1946), riming electrification (Reynolds et al, 1955;Takahashi, 1978a) and others.…”
Section: Introductionmentioning
confidence: 99%
“…Whipple (1944) indicated that there were some problems in deducing the electric charge on precipitation elements in thunderstorm from the measurement of their electric charge at the ground. Gunn (1951) has attempted to measure the electric charge on precipitation elements in clouds with the use of an aeroplane.…”
Section: Introductionmentioning
confidence: 99%